If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(8 + 2.5y) = 16 (8 * 2 + 2.5y * 2) = 16 (16 + 5y) = 16 Add '-16' to each side of the equation. 16 + -16 + 5y = 16 + -16 Combine like terms: 16 + -16 = 0 0 + 5y = 16 + -16 5y = 16 + -16 Combine like terms: 16 + -16 = 0 5y = 0 Solving 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = 0 Simplifying y = 0
| -42=-36t | | 0-3(0)=6 | | 6t+2=2(3t+1) | | y=7-x/2 | | 3z^2+5z+1=3 | | 2x+x+4x=1715 | | 4x-3-6x+2=0 | | 0.25t+0.833=1.5t+0.67 | | (7-2j)-(7+2j)= | | 6x+8=4x+4-2x | | (y*2)+y=957 | | x+(x-3)=31 | | (x-3)(x-3)=20 | | 79-2x=10x-19 | | -5=z/3 | | 2g-32=-32 | | x-(x-1)=81 | | -6x+11=4x | | -2x/x-1+x+3/x^2-1 | | (y+9)+y=37 | | 6x-2=15-110 | | -16+x=43 | | 2x-5y=14 | | x-(x-1)=41 | | (2x+8)(x+4)=0 | | 27=9+x | | 2m^2-15m-27=0 | | -3m(n-2)=3n-5n+9 | | 6c+5u=-49 | | (x-67)+x=261 | | 3(2x-1)-(2-x)-7x=0 | | x+(x-1)=81 |